1997
DOI: 10.1203/00006450-199710000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phenylalanine Hydroxylase Genotypes and Hyperphenylalaninemia Phenotypes Using L-[1-13C]Phenylalanine Oxidation Rates in Vivo: A Pilot Study1

Abstract: Hyperphenylalaninemia (HPA) resulting from deficient activity of phenylalanine hydroxylase (PAH) is caused by mutations in the human PAH gene (McKusick 261600). Herein, we report a noninvasive method to: 1) estimate whole-body phenylalanine oxidation in patients with HPA and 2) compare effects of mutant genotypes on phenotypes. We used oral L-[1-13C]phenylalanine as a substrate and measured 13CO2 formation in the first hour as an index of phenylalanine oxidation rates in: 1) patients with PKU (n = 6), variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…However, since the in vitro PAH activity is proportional to in vivo PAH activity in hepatocytes, as demonstrated by the correlation of genotype and biochemical phenotype, the predicted PAH activity system is useful for assessing the relative severity of PKU mutations, the classification of PKU, and the prediction of the clinical course. Secondly, there are cases with discordance between genotype and biochemical phenotype (Kayaalp et al 1997;Treacy et al 1997). Treacy et al (1996) have demonstrated different in vivo metabolic profiles for phenylalanine arising from differences in phenylalanine transamination and renal clearance of transamination metabolites in two siblings with a different PKU phenotype but the same genotype.…”
Section: Discussionmentioning
confidence: 97%
“…However, since the in vitro PAH activity is proportional to in vivo PAH activity in hepatocytes, as demonstrated by the correlation of genotype and biochemical phenotype, the predicted PAH activity system is useful for assessing the relative severity of PKU mutations, the classification of PKU, and the prediction of the clinical course. Secondly, there are cases with discordance between genotype and biochemical phenotype (Kayaalp et al 1997;Treacy et al 1997). Treacy et al (1996) have demonstrated different in vivo metabolic profiles for phenylalanine arising from differences in phenylalanine transamination and renal clearance of transamination metabolites in two siblings with a different PKU phenotype but the same genotype.…”
Section: Discussionmentioning
confidence: 97%
“…Neither RBC gal-1-P nor urine galactitol increased within 24 h of testing. Other metabolic disorders that express a serious problem in newborns have been studied following bolus or sustained exposure to trace amount of precursors in blocked reactions (18,19). Children with maple syrup urine disease and phenylketonuria had no adverse events to bolus or sustained infusions of leucine or phenylalanine respectively at these trace doses for 13 C detection in breath.…”
Section: Discussionmentioning
confidence: 99%
“…The R157N MBP-PAH band was repeatedly reduced in intensity after Coomassie staining of SDS-PAGE gels, despite the loading of apparently equal amounts of protein as determined by the Bradford assay. Normal absolute values are provided in Treacy et al, (1997). e Not detectable; threshold is 3% of normal.…”
Section: Expression Of Mbp-pah Fusion Proteins In E Colimentioning
confidence: 99%